221k views
1 vote
-Quadratic Equations- Solve each by factoring, write each equation in standard form first.

-Quadratic Equations- Solve each by factoring, write each equation in standard form-example-1

1 Answer

1 vote

Answer

The solutions to the quadratic equations are


\begin{gathered} a^2-4a-45 \\ \text{Solution: }a=-5\text{ or }9 \\ \\ 5y^2+4y=0 \\ \text{Solution: }y=0\text{ or }-(4)/(5) \end{gathered}

SOLUTION

Problem Statement

The question gives us 2 quadratic equations and we are required to solve them by factoring, first writing them in their standard forms.

The quadratic equations given are:


\begin{gathered} a^2-4a-45=0 \\ 5y^2+4y=0 \end{gathered}

Method

To solve the questions, we need to follow these steps:

(We will represent the independent variable as x for this explanation. We know they are "a" and "y" in the questions given)

The steps outlined below are known as the method of Completing the Square.

Step 1: Find the square of the half of the coefficient of x.

Step 2: Add and subtract the result from step 1.

Step 3: Re-write the Equation. This will be the standard form of the equation

Step 4. Solve for x

We will apply these steps to solve both questions.

Implementation

Question 1:


\begin{gathered} a^2-4a-45=0 \\ \text{Step 1: Find the square of the half of the coefficient of }a \\ (-(4)/(2))^2=(-2)^2=4 \\ \\ \text{Step 2: Add and subtract 4 to the equation} \\ a^2-4a-45+4-4=0 \\ \\ \text{Step 3: Rewrite the Equation} \\ a^2-4a+4-45-4=0 \\ (a^2-4a+4)-49=0 \\ (a^2-4a+4)=(a-2)^2 \\ \therefore(a-2)^2-49=0 \\ \text{ In standard form, we have:} \\ (a-2)^2=49 \\ \\ \text{Step 4: Solve for }a \\ (a-2)^2=49 \\ \text{ Find the square root of both sides} \\ \sqrt[]{(a-2)^2}=\pm\sqrt[]{49} \\ a-2=\pm7 \\ \text{Add 2 to both sides} \\ \therefore a=2\pm7 \\ \\ \therefore a=-5\text{ or }9 \end{gathered}

Question 2:


\begin{gathered} 5y^2+4y=0 \\ \text{ Before we begin solving, we should factorize out 5} \\ 5(y^2+(4)/(5)y)=0 \\ \\ \text{Step 1: Find the square of the coefficient of the half of y} \\ ((4)/(5)*(1)/(2))^2=((2)/(5))^2=(4)/(25) \\ \\ \text{Step 2: Add and subtract }(4)/(25)\text{ to the equation} \\ \\ 5(y^2+(4)/(5)y+(4)/(25)-(4)/(25))=0 \\ \\ \\ \text{Step 3: Rewrite the Equation} \\ 5((y^2+(4)/(5)y+(4)/(25))-(4)/(25))=0 \\ 5(y^2+(4)/(5)y+(4)/(25))-5((4)/(25))=0 \\ 5(y^2+(4)/(5)y+(4)/(25))-(4)/(5)=0 \\ \\ (y^2+(4)/(5)y+(4)/(25))=(y+(2)/(5))^2 \\ \\ \therefore5(y+(2)/(5))^2-(4)/(5)=0 \\ \\ \text{ In standard form, the Equation becomes} \\ 5(y+(2)/(5))^2=(4)/(5) \\ \\ \\ \text{Step 4: Solve for }y \\ 5(y+(2)/(5))^2=(4)/(5) \\ \text{ Divide both sides by 5} \\ (5)/(5)(y+(2)/(5))^2=(4)/(5)*(1)/(5) \\ (y+(2)/(5))^2=(4)/(25) \\ \\ \text{ Find the square root of both sides} \\ \sqrt[]{(y+(2)/(5))^2}=\pm\sqrt[]{(4)/(25)} \\ \\ y+(2)/(5)=\pm(2)/(5) \\ \\ \text{Subtract }(2)/(5)\text{ from both sides} \\ \\ y=-(2)/(5)\pm(2)/(5) \\ \\ \therefore y=0\text{ or }-(4)/(5) \end{gathered}

Final Answer

The solutions to the quadratic equations are


\begin{gathered} a^2-4a-45 \\ \text{Solution: }a=-5\text{ or }9 \\ \\ 5y^2+4y=0 \\ \text{Solution: }y=0\text{ or }-(4)/(5) \end{gathered}

User Indhi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.